Mechanical Behavior of Particulate Aluminium‐Epoxy Hybrid Foams Based on Cold‐Setting Polymers1 . Issue 10 (8th May 2017) - Weise, Jörg; Queiroz Barbosa, André Felipe; Yezerska, Olga; Lehmhus, Dirk; Baumeister, Joachim
Abstract : New types of hybrid foams with cold‐setting polymer foam matrix have been developed. These are based on AlSi10 foam granules and a cold‐setting epoxy polymer foam phase. The mechanical characteristics of the hybrid foams like stiffness, compressive, and tensile strength were determined using quasi‐static compression and tensile tests. Their overall mechanical behavior is compared to APM‐(Advanced Pore Morphology)‐based hybrid foams comprising similar aluminium foam granules in combination with single component hot setting epoxy foams. While the latter generally outperform the cold‐setting variants at their present state of development, the ease of manufacturing in conjunction with promising levels of strength, and stiffness will support future application of the new material. Abstract : Hybrid foam consisting of aluminium foam and cold‐setting epoxy polymer foam can be used for the filling and reinforcement of hollow structures. While Foaminal TM aluminium foam outperforms the hybrid foam, the ease of manufacturing and promising level of strength and stiffness support future application of the new material.